The influence of store atmosphere, promotion, and location Kenari Jaya Bordir on buying interest - Khoirul Anwar (Enrichment : Journal of Management, 2022)
The phenomenon that occurs at "Kenari Jaya Bordir" in Rembang District, Pasuruan Regency based on the results of interviews with the owner of "Kenari Jaya Bordir" can be several problems, such as the Store Atmosphere is comfortable with the right lighting, beautiful exterior and interior, the store has carried out promotions banner installation, the location of the "Kenari Jaya Bordir" shop is also quite strategic in the shop area so that it is easy to reach, however, customers and sales are still relatively small compared to competitors around it. The population in this study were "Kenari Jaya Bordir" consumers, who made purchases from 8 to 21 October 2022. The sampling technique used non-probability sampling with a purposive side method which was judgmental sampling so that 47 respondents were obtained.